Securing the North Natuna Sea: Indonesia's Defense Diplomacy Strategy - Sarjito, Aris (Jurnal Administrasi Publik dan Bisnis, 2024)
ABSTRACT This research delves into the Evolution of Indonesia's Defense Diplomacy Strategy in the North Natuna Sea, employing Historical Institutionalism to analyze the historical trajectory. The study also adopts a Neorealist Perspective to assess the Current State of Defense Cooperation and Alliances in the region, shedding light on geopolitical dynamics. A Legal Positivist Perspective evaluates Adherence to International Maritime Laws and Defense Diplomacy. Additionally, Cultural Diplomacy, Soft Power, and their influence on Indonesia's Defense Diplomacy in the North Natuna Sea are examined, emphasizing implications for Perception and Support. Qualitative research methods, including document analysis and expert interviews, guide the investigation. Findings reveal a nuanced historical development, realist power dynamics, legal frameworks, and the crucial role of cultural diplomacy. The research underscores the need for a comprehensive and adaptive defense diplomacy strategy to secure the North Natuna Sea. KEYWORDS: Defense Diplomacy, International Maritime Laws, North Natuna Sea, Soft Power